An unusual case of refractory status epilepticus in a young lady: Anti-NMDA receptor encephalitis - Khoo C.S.; Zulkifli N.H.; Siti Soraya Ab Rahman (Royal College of Physicians, 2024)
Indexed by SCOPUS